A Palaeoenvironmental Investigation of Two Prehistoric Burnt Mound Sites in Northern Ireland. Issue 6 (21st June 2016) - Wheeler, J.; Timpany, S.; Mighall, T. M.; Scott, L.
Abstract : This paper provides a summary of the palaeoenvironmental evidence from a spread of late Mesolithic burnt material and two late Neolithic to early Bronze Age burnt mounds. The burnt mounds were up to 10 m diameter, had an amorphous shape, and were consistently less than 0.8 m thick. Monoliths were collected from two sites, Ballygawley and Roughan, in Co. Tyrone, Northern Ireland. This provided an opportunity to use a detailed palaeoecological approach for the first time to investigate the use and function of burnt mounds. Pollen, non‐pollen palynomorphs, micro‐ and macroscopic charcoal were used to place these features within their environmental context, and to establish if such an approach could provide further insights into their function. The palynological results shared similar characteristics: high microscopic charcoal values, repetitive fluctuations in tree and shrub taxa, increased Sphagnum, and the presence of non‐pollen palynomorphs (NPPs) HdV‐114 and HdV‐146, all of which could be diagnostic indicators of burnt mounds in palynological records. While the data do not allow us to ascribe a specific function for the burnt mounds, their environmental setting is discussed. A "see‐saw" pattern of arboreal pollen, combined with the macroscopic charcoal data, indicate possible species selection and management of local woodland for fuelwood.